ONLINE TIRE SALES PLAN AT CINERE RACING SHOP USING VUE.JS TECHNOLOGY - Wisnu Sukma Maulana (International Journal Multidisciplinary Science, 2023)
The era of e-commerce or what is known as selling goods online is currently experiencing very significant development. Urban and village communities have begun to change direction in buying and selling from offline to online. One of the technologies used in ecommerce is website-based technology. Websites can be created and formulated with various features ranging from product catalogs to real-time payments very instantly. Websites have experienced a very rapid evolution from previously only being textual to now being able to make buyers feel a real experience as if they were shopping directly at the store. Website technology with the vue.js framework is a variant that is currently quite popular with programmers. Vue.js itself comes from early website technology, namely JavaScript. This has a significant impact where almost all website viewing browsers adopt JavaScript technology. One of the shops being tested using the vue.js technology design is the Cinere Racing Tire Shop. The Cinere Racing Tire Shop wants to develop the introduction of its shop services not only locally but if possible, on a national scale. By introducing the shop online, it is hoped that tire sales transactions will increase sharply. The vue.js technology design also adopts the Scrum Agile way of working according to the principles of computer science, especially the subject matter regarding the development cycle of creating a system or application.